Ethnolinguistic Pluralism and Multiculturalism in Contemporary Indonesia: A Case Study of Minority Javanese Muslim Migrants in Bali - I Nyoman Wijaya; Sri Lestari; Mosli Tarsat (Indonesian Historical Studies, 2025)
This article examines how majority-minority relations in Bali, Indonesia, have changed in the last decade, in the context of multiculturalism and multilingualism. It does so through a case study of the socio-cultural practices of minority Muslim migrants in a predominantly Hindu community in the village of Sumerta, which is part of Bali’s capital city of Denpasar. The study shows fresh evidence for the dynamic nature, issues and challenges of inter-ethnic/religious relations at the most local level, a matter of great significance in debates on cultural pluralism, multilingualism, tolerance and modern democracy on the broader national and global levels. Our discussion and analysis makes use of methodological and theoretical insights from socio-ethno-linguistics, in combination with history and cultural studies. We argue that the cultural-religious and social practices of the different ethnolinguistic groups in this village are based on culturally plural community interactions, where the different ethnic and religious groups remain separate. Intergroup relations, however, show positive forms of cultural and linguistic engagement, primarily symbolic in nature, and thus tend towards multilingualism as an indicator of multiculturalism.